Health care disparities among octogenarians and nonagenarians with stage II and III rectal cancer. Issue 22 (31st July 2017) - Cassidy, Richard J.; Switchenko, Jeffrey M.; Cheng, En; Jiang, Renjian; Jhaveri, Jaymin; Patel, Kirtesh R.; Tanenbaum, Daniel G.; Russell, Maria C.; Steuer, Conor E.; Gillespie, Theresa W.; McDonald, Mark W.; Landry, Jerome C.
Abstract : BACKGROUND: Octogenarians and nonagenarians with stage II/III rectal adenocarcinomas are underrepresented in the randomized trials that have established the standard‐of‐care therapy of preoperative chemoradiation followed by definitive resection (ie, chemoradiation and then surgery [CRT+S]). The purpose of this study was to evaluate the impact of therapies on overall survival (OS) for patients with stage II/III rectal cancers and determine predictors of therapy within the National Cancer Data Base (NCDB). METHODS: In the NCDB, patients who were 80 years old or older and had clinical stage II/III rectal adenocarcinoma from 2004 to 2013 were queried. Kaplan‐Meier analysis, log‐rank testing, logistic regression, Cox proportional hazards regression, interaction effect testing, and propensity score–matched analysis were conducted. RESULTS: The criteria were met by 2723 patients: 14.9% received no treatment, 29.7% had surgery alone, 5.0% underwent short‐course radiation and then surgery (RT+S), 45.3% underwent CRT+S, and 5.1% underwent surgery and then chemoradiation (S+CRT). African American race and residence in a less educated county were associated with not receiving treatment. Male sex, older age, worsening comorbidities, and receiving no treatment or undergoing surgery alone were associated with worse OS. There was no statistical difference in OS between RT+S, S+CRT, and CRT+S. Interaction testing found that CRT+S improved OS independently of age, comorbidity status, sex, race, and tumor stage. In the propensity score–matched analysis, CRT+S was associated with improved OS in comparison with surgery alone. CONCLUSIONS: A significant portion of octogenarians and nonagenarians with stage II/III rectal adenocarcinomas do not receive treatment. African American race and living in a less educated community are associated with not receiving therapy. This series suggests that CRT+S is a reasonable strategy for elderly patients who can tolerate therapy. Cancer 2017;123:4325‐36 . © 2017 American Cancer Society . Abstract : Octogenarians and nonagenarians with stage II/III rectal adenocarcinomas are underrepresented in the clinical trials establishing preoperative chemoradiation and then resection as the standard of care. In this analysis of the National Cancer Data Base of patients who are 80 years old or older and have stage II/III rectal cancer, the receipt of chemoradiation followed by surgery improves overall survival, and this is confirmed by multivariate analysis, interaction effect testing, and propensity score–matched analysis. Almost 15% of these elderly patients do not receive any cancer‐directed care, with African American race and living in a less educated census tract placing a patient at risk for not receiving care.